1989
DOI: 10.1007/bf00396705
|View full text |Cite
|
Sign up to set email alerts
|

Zur Biochemie der Thiolgruppe: Bedeutung des Glutathions

Abstract: Glutathione (GSH) comprises the bulk of the pool of free thiol groups in biological systems. Since its first description as philothione 100 years ago, there have been repeated surprises in discoveries of novel functions. Just recently the important role of thioethers with products of the lipoxygenase reaction, i.e., the leukotrienes, was revealed as mediator of physiological and pathophysiological processes. Another major function resides in detoxication, GSH being cosubstrate in the GSH-peroxidase reaction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 96 publications
0
15
0
Order By: Relevance
“…It has been reported that some thiol compounds, such as GSH and N-acetylcysteine (NAC), can protect cells from oxidative stress by scavenging free radicals and by enzymatic reactions. Glutathione is the most important cellular thiols, modulating redox-regulated signal transduction, acting as a substrate for several peroxidases and other enzymes that prevent or mitigate the deleterious effects of ROS [44], [45]. The ratio of GSH/GSSG in the plasma can reflect changes in the stability of the redox status of an organism [46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some thiol compounds, such as GSH and N-acetylcysteine (NAC), can protect cells from oxidative stress by scavenging free radicals and by enzymatic reactions. Glutathione is the most important cellular thiols, modulating redox-regulated signal transduction, acting as a substrate for several peroxidases and other enzymes that prevent or mitigate the deleterious effects of ROS [44], [45]. The ratio of GSH/GSSG in the plasma can reflect changes in the stability of the redox status of an organism [46].…”
Section: Discussionmentioning
confidence: 99%
“…GSH also conjugates with electrophiles and thus participates in the metabolism and detoxification of endogenous compounds and xenobiotic toxicants [1416]. In addition, GSH is involved in many other metabolic reactions [9, 17, 18]. Therefore, it is not surprising that GSH plays roles in various cellular processes such as cell growth, proliferation, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its function as an antioxidant, it is responsible for the maintenance of intracellular thiol redox status and thus for the function of many biological processes within the cell [3,4]. For most of its functions glutathione must be in the reduced form.…”
Section: Introductionmentioning
confidence: 99%